ANALYSIS OF TRANSFORMATIONAL LEADERSHIP ON JOB SATISFACTION MEDIATED BY SOFT SKILLS DEVELOPMENT FOR MILLENNIAL EMPLOYEES AT THE AGD GOVERNMENT INSTITUTION - Gerrin Djaya, Angela (Jurnal Manajemen, 2025)
The study aims to analyze the influence of transformational leadership mediated by soft development skills on millennial employee job satisfaction at the AGD Government Institution. The research method used was quantitative with survey techniques. Data collected from 100 millennial employees at the AGD Government Institution through questionnaires. The data analysis technique used is the Process Macro SPSS which was developed by Andrew Hayes to test the transformational leadership influence, the soft development skills on millennial employee job satisfaction. Research suggests that transformational leadership and soft development skills have a significant and significant impact on the job satisfaction of millennial employees. The findings suggest that transformational leadership and the development of soft skills are key factors in promoting millennial employee job satisfaction. The implications of this study are the importance of institutions implementing leadership transformation and developing millennial worker soft skills to increase their job satisfaction.